Promethee Algorithm in Assessing Lecturer Performance - Fatkhurrochman Fatkhurrochman; Wahyu Priyoatmoko; Sugeng Wahyudiono (International Journal of Computer and Information System (IJCIS), 2022)
Higher Education is an educational institution that plays a role in producing quality human resources. The roles, duties and responsibilities of lecturers are very important in educating the nation's life and national goals. There are many problems that cause the performance of lecturers at universities in Indonesia. Meanwhile, lecturers are required to give good performance. In this case, the researcher is interested in evaluating the performance of lecturers using the promethee method. The promethee method is able to produce decisions based on comparisons between alternatives according to the preference function and the different weights of each criterion. The criteria used in the assessment of lecturer performance are 10 criteria with 7 alternative lecturers. The Promethee method produces recommendations for lecturers with the best performance, namely Lecturer E who has a net flow value of 0.12153. While the lecturer with the lowest performance assessment is Lecturer B with a net flow value of -0.19167. The results of the decisions given by the promethee method can help provide an assessment of the lecturer's performance from the several alternatives given. So as to be able to produce an objective recommendation decision